PENGARUH TANGIBILITY, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR KEUANGAN - EKO SUPRIYANTO; FALIKHATUN FALIKHATUN (Jurnal Bisnis dan Akuntansi, 2008)
The research examines influencing of tangibility, sales growth, company size to financial structure. Research conducted at food and beverages industries which go public in Jakarta Stock Exchange. The determination of sample in this research use purposive sampling method. The total of samples is 11 companies. Data were analyzed using multiple regression analysis. The results of the research show tangibility, sales growth and company size influenced to the company’s financial structure. Managers of food and beverages industries should consider in arranging the company financial structure. They can use based on these findings, especially more attention on company size to manage that financial structure. Also, increasing the proportion of tangibility is important. It can add capacity of production, so that can increase in products selling and profitability.